2009
DOI: 10.1080/17483100802613701
|View full text |Cite
|
Sign up to set email alerts
|

Children's perceptions of their use of assistive devices in home and school settings

Abstract: The results demonstrate the significance of child-environment interaction. The children's attitudes towards device usage are influenced by their perceptions of the contextual feature of both settings. Additionally, the results indicate that children's views about their assistive devices may be different from those of adult users due to their different developmental stages and unique personal experiences. The findings suggest the importance of children's active participation in the field of assistive device res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
40
0
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 25 publications
0
40
0
4
Order By: Relevance
“…This social stigma was also reported by Chinese children with leukaemia (Wu et al, 2010) and Taiwanese children with celebral palsy (Huang et al, 2009). Sick children might also witness the death of close friends who share their illness (Wicks, 2007).…”
Section: What Are the Needs Of Children Who Have Life Limiting Illnesmentioning
confidence: 96%
See 1 more Smart Citation
“…This social stigma was also reported by Chinese children with leukaemia (Wu et al, 2010) and Taiwanese children with celebral palsy (Huang et al, 2009). Sick children might also witness the death of close friends who share their illness (Wicks, 2007).…”
Section: What Are the Needs Of Children Who Have Life Limiting Illnesmentioning
confidence: 96%
“…Consequently some parents want teachers to encourage children to complete diaries as a way of keeping teachers aware of what was happening to the child, such as emergency hospital visits or treatment, when out of school. Mothers of children with cerebral palsy in Taiwan (Huang et al, 2009) and England (Rózsagegyi, 2008) want better communication with tea he s to e su e that the ha e app op iate esou es a d the hild s p a ti e ith assisti e devices such as wheelchairs or walkers is continued whilst at school. Some English parents are concerned that their communication with teachers is reduced when their sick child reaches 16 years old and so begins to be accorded the confidentiality given to adults (Asprey and Nash, 2006).…”
Section: What Are the Needs Of Teachers Who Are Teaching Children Witmentioning
confidence: 99%
“…As alterações apresentadas por pessoas com SD podem representar problemas com respeito à sua funcionalidade e independência para a realização das Atividades da Vida Diária (AVDs), mesmo durante a vida adulta [2]. Com a prática de atividade física, o indivíduo com SD se torna capaz de conhecer melhor o mundo em que vive, a partir do momento em que passa a conhecer seu corpo e suas capacidades intelectuais por meio dos movimentos [3]. Estudos mostram que uma estimulação precoce adequada é capaz de gerar melhoras no desenvolvimento motor de crianças com SD e que, por meio da experiência ativa obtida por estimulação, pode-se construir um novo padrão de comportamento, levando-as a modificações funcionais para a realização de AVDs [4].…”
Section: Introductionunclassified
“…16 (p.8) Another study found that children use assistive devices more often at school than at home; 17 factors in the physical environment, the desired level of independence, and mothers' attitudes also influenced device use. 17 In the present study we included all people with standing devices, regardless of medical diagnosis, in contrast to previous studies that focused on people with specific diagnoses. Our study addresses the use of standing devices from the points of view of people with varying levels of independence and restricted mobility, focusing on the social and personal impacts of using standing devices.…”
mentioning
confidence: 98%
“…It is also important to consider environmental factors for the user. 17,25 Reasons given for standing…”
Section: Extent Of Usementioning
confidence: 99%